2018
DOI: 10.1016/j.neuron.2018.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Chd2 Is Necessary for Neural Circuit Development and Long-Term Memory

Abstract: Summary Considerable evidence suggests loss of function mutations in the chromatin remodeler, CHD2, contribute to a broad spectrum of human neurodevelopmental disorders. However, it is unknown how CHD2 mutations lead to impaired brain function. Here we report mice with heterozygous mutations in Chd2 exhibit deficits in neuron proliferation and a shift in neuronal excitability that included divergent changes in excitatory and inhibitory synaptic function. Further in vivo experiments show Chd2+/− mice displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 64 publications
(96 reference statements)
1
56
0
Order By: Relevance
“…Other work has shown that the TSC1-mTOR pathway, which has been implicated in autism, normally represses inhibitory synapses onto excitatory neurons, such that deficiency of Tsc1 leads to decreased inhibition and network hyperexcitability [58]. Mice lacking CHD2, a chromatin remodeling and autism risk gene, had fewer cortical and hippocampal interneurons, and a reduction in miniature IPSC frequency; the mutants' cognitive phenotype was partially rescued by interneuron transplantation [59]. Finally, a large body of work has shown that Rett syndrome, which involves some autism-like features, includes deficits in inhibitory interneuron development and function [60], and that many abnormal behaviors in mice are driven by the loss of MeCP2 specifically in interneurons [61].…”
Section: Altered E-i Balance In Mouse Models Of Autism (Asd)mentioning
confidence: 99%
“…Other work has shown that the TSC1-mTOR pathway, which has been implicated in autism, normally represses inhibitory synapses onto excitatory neurons, such that deficiency of Tsc1 leads to decreased inhibition and network hyperexcitability [58]. Mice lacking CHD2, a chromatin remodeling and autism risk gene, had fewer cortical and hippocampal interneurons, and a reduction in miniature IPSC frequency; the mutants' cognitive phenotype was partially rescued by interneuron transplantation [59]. Finally, a large body of work has shown that Rett syndrome, which involves some autism-like features, includes deficits in inhibitory interneuron development and function [60], and that many abnormal behaviors in mice are driven by the loss of MeCP2 specifically in interneurons [61].…”
Section: Altered E-i Balance In Mouse Models Of Autism (Asd)mentioning
confidence: 99%
“…Further, observations in human stem cell-derived models (e.g., organoids) will be key to identify species-specific alterations that define the unique features of social behavior in humans. CHD2 proliferation KO mice [189] PTEN survival KO mice [193] TBR1 lamination KO mice [70,77] Author…”
Section: Resultsmentioning
confidence: 99%
“…were enriched for various RNA-related GO categories (Supplementary Table 1). Notably, changes in E13.5 embryo were significantly anti-correlated with those in E13.5 medial ganglionic eminence (MGE) of Chd2 +/mice 22 (Spearman R=-0.27, P<10 -100 ). Milder anticorrelation was observed between dysregulation in the Chaserr +/adult brain and the Chd2 +/adult hippocampus 22 (R= -0.11, P= 8.8×10 -47 ).…”
Section: Relative Expressionmentioning
confidence: 99%
“…Notably, changes in E13.5 embryo were significantly anti-correlated with those in E13.5 medial ganglionic eminence (MGE) of Chd2 +/mice 22 (Spearman R=-0.27, P<10 -100 ). Milder anticorrelation was observed between dysregulation in the Chaserr +/adult brain and the Chd2 +/adult hippocampus 22 (R= -0.11, P= 8.8×10 -47 ). Hundreds of genes were dysregulated in the Chaserr -/-Chd2 m/m mEFs compared to WT mEFs from the same pregnancies, and these changes are likely due to Chd2 loss-of-function, as there was no correlation between these changes and the changes in Chaserr -/-mEFs (Spearman R=-0.003 P=0.68, Fig.…”
Section: Relative Expressionmentioning
confidence: 99%